Coaching Model : Metode Mitra Belajar Agama Kolaboratif pada Program Tutorial PAI Pembelajaran Agama Islam Universitas Jambi - Sobri, Muhammad; Iryani, Eva; Supian; Rafii, Muhammad (Institut Agama Islam Yasni Bungo, 2022)
The urgency of guidance/coaching-based religious learning in higher education is absolutely in the demands of the current era of collaboration. Where the rapid flow of information and digitalization leads students to deviant religious behavior without being aware of the weak control and input of students' basic religious beliefs. This study aims to provide an explanation of the concept and implementation of the coaching model along with its supports and implementation constraints in the Jambi University Islamic Education tutorial program in providing basic religious guidance through collaboration between PAI lecturers and coaches/tutors within the framework of coaching modeling. The method used in this study is based on descriptive qualitative research methods. Which aims to explain a phenomenon as deeply as possible by collecting data as deeply as possible, which shows the importance of the depth and detail of the data being studied according to their needs. : (1) in-depth interviews; (2) observation; (3) documentation is used as the data collection technique. The results of this study indicate that first, the implementation of coaching models in tutorial activities is carried out with active and participatory collaboration between lecturers, tutors/coaches and students/coachees with an increase in religiosity through a fortopolio-based assessment of religious proficiency (FKB). Second, the obstacles that become obstacles are related to the effectiveness and efficiency of time and the quality of input for the low initial ability of students. and Finally, the support carried out with this activity is the availability of adequate infrastructure and textbooks, and the greatest support is from competent and professional Coach/Tutor resources by passing recruitment and selective competency tests.